Mitigating the African Economic Crisis Through Financial Inclusion - Collins Okechukwu Irem; Friday Ogbu Edeh; Nakacwa Kasozi Sherifah; Gloria Ifeoma Duruzor; Charles Chukwuma Nwoba; Chris U.A Ukaidi; Desmond Neji Oben (AIBPM Publisher, 2024)
This study sought to examine the challenges facing the African economy and financial inclusion. The paper undertakes a comprehensive exploration of the African economic landscape, navigating through historical intricacies, structural challenges, and global influences. Grounded in a quantitative methodology, the study adopted the survey method to systematically unravel the multifaceted dimensions of the economic crisis and financial inclusion in Africa. The study was anchored on both Monetarist and Keynesian models. A sample size of 350 participants was studied, using a purposive sampling technique. The study discovered that cultural, technological, and regulatory limits all significantly contribute to the economic crisis, which is evidenced by the high rate of currency devaluation in Africa, high rates of inflation in the price of goods, and economic downturns. Thus, the paper recommends that fin-tech companies, appropriate technology applications, and advancements in online payments could potentially save this predicament. The paper further recommends that the government should enact regulatory changes that lower entrance barriers for financial institutions, support innovation, and safeguard consumers to advance financial inclusion.